Identifikasi Senyawa Bioaktif dan Evaluasi Kapasitas Antioksidan Seduhan Simplisia Bunga Telang (Clitoria ternatea L.) - Yuliasari, Hikmah; Ayuningtyas, Laksmi Putri; Erminawati, Erminawati (Jurnal Teknologi Pangan dan Hasil Pertanian, 2023)
Butterfly pea (Clitoria ternatea L.) is an indigenous Indonesian flower that is usually consumed as a natural ingredient in herbal drinks and nutraceutical products. It contains several bioactive compounds that showed strong antioxidant activity to neutralize free radical compounds from foods. The aim of this study was to identify the bioactive compounds, antioxidant capacity and the organoleptic characteristics in the brewed of dried butterfly pea. The experimental design of this study used a completely randomized design with two factors: 1) dried butterfly pea content in water : 0,5; 1,0; dan 1,5 (g/200 ml) and 2) brewing levels (1, 2, and 3 times). The phytochemical screening analysis revealed that the brewed butterfly pea contained bioactive compounds such as flavonoids, tannins, saponins, steroids, and triterpenoids. The longer dried butterfly peas soak in water showed the higher level of total anthocyanin content, total phenolic compounds, and antioxidant activity. Organoleptic analysis showed significantly effect of the colour but not the odour or flavour of the brewed dry butterfly pea.